Accelerated flows at Jupiter's magnetopause: Evidence for magnetic reconnection along the dawn flank. Issue 10 (25th May 2017) - Ebert, R. W.; Allegrini, F.; Bagenal, F.; Bolton, S. J.; Connerney, J. E. P.; Clark, G.; DiBraccio, G. A.; Gershman, D. J.; Kurth, W. S.; Levin, S.; Louarn, P.; Mauk, B. H.; et al.
Abstract: We report on plasma and magnetic field observations from Juno's Jovian Auroral Distributions Experiment and Magnetic Field Investigation at 18 magnetopause crossings when the spacecraft was located at 6 h magnetic local time and 73–114 Jovian radii from Jupiter. Several crossings showed evidence of plasma energization, accelerated ion flows, and large magnetic shear angles, each representing a signature of magnetic reconnection. These signatures were observed for times when the magnetosphere was in both compressed and expanded states. We compared the flow change magnitudes to a simplified Walén relation and found 60% of the events to be 110% or less of the predicted values. Close examination of two magnetopause encounters revealed characteristics of a rotational discontinuity and an open magnetopause. These observations provide compelling evidence that magnetic reconnection can occur at Jupiter's dawn magnetopause and should be incorporated into theories of solar wind coupling and outer magnetosphere dynamics at Jupiter. Key Points: Observations at Jupiter's dawn magnetopause by Juno revealed accelerated ion flows and large magnetic shear angles at several crossings Case studies of two magnetopause crossings showed evidence of rotational discontinuities and an open magnetopause Compelling evidence for magnetic reconnection at the Jupiter's dawn magnetopause during Juno's approach to Jupiter and first capture orbit